Larval chaetotaxy and morphology are highly homoplastic yet phylogenetically informative in Hydrobiusini water scavenger beetles (Coleoptera: Hydrophilidae). Issue 2 (25th December 2020) - Archangelsky, Miguel; Martínez Román, Nicolás Rafael; Fikáček, Martin
Abstract: Phylogenetic analyses testing the monophyly of the tribe Hydrobiusini and the relationships among its genera are performed based on a data matrix including characters of larval morphology and morphometrics, larval chaetotaxy and adult morphology, including eight of the nine hydrobiusine genera plus 15 outgroup taxa. The head chaetotaxy of six genera of the tribe Hydrobiusini is described ( Ametor, Hybogralius, Hydramara, Limnohydrobius, Limnoxenus and Sperchopsis ). Morphometric characters derived from the head capsule and mouthparts are included. All characters are illustrated in detail. The analyses performed on the above datasets and their combinations reveal the monophyly of the Hydrobiusini except for Hybogralius, and reconstruct the internal topology of the tribe, largely corresponding to results of previous molecular analyses. Hybogralius groups with genera having larvae adapted to underwater feeding in all analyses. The position of the genus Tritonus within the Laccobiini is questioned by our analyses, which suggest a closer relationship with the tribes Hydrophilini or Hydrobiusini. Larval characters are revealed as highly homoplastic, with chaetotaxic characters performing slightly worse than usual larval morphology. Nonetheless, they are phylogenetically informative and useful for testing phylogenetic hypotheses resulting from analyses of molecules or adult morphology. A key to larvae of the genera of the Hydrobiusini is presented.